Reducing the knowledge to action gap in hospital nutrition care – Developing and implementing nutritionDay 2.0. Issue 3 (March 2021) - Moick, S.; Hiesmayr, M.; Mouhieddine, M.; Kiss, N.; Bauer, P.; Sulz, I.; Singer, P.; Simon, J.
Summary: Background & aims: In hospital nutrition care the difficulty of translating knowledge to action often leads to inadequate management of patients with malnutrition. nutritionDay, an annual cross-sectional survey has been assessing nutrition care in healthcare institutions in 66 countries since 2006. While initial efforts led to increased awareness of malnutrition, specific local remedial actions rarely followed. Thus, reducing the Knowledge-to-action (KTA) gap in nutrition care requires more robust and focused strategies. This study describes the strategy, methods, instruments and experience of developing and implementing nutritionDay 2.0, an audit and feedback intervention that uses quality and economic indicators, feedback, benchmarking and self-defined action strategies to reduce the KTA gap in hospital nutrition care. Methods: We used an evidence based multi-professional mixed-methods approach to develop and implement nutritionDay 2.0 This audit and feedback intervention is driven by a Knowledge-to-Action framework complemented with robust stakeholder analysis. Further evidence was synthesized from the literature, online surveys, a pilot study, World Cafés and individual expert feedback involving international health care professionals, nutrition care scientists and patients. Results: The process of developing and implementing nutritionDay 2.0 over three years resulted in a new audit questionnaire based on 36 nutrition care quality and economic indicators at hospital, unit and patient levels, a new action-oriented feedback and benchmarking report and a unit-level personalizable action plan template. The evaluation of nutritionDay 2.0 is ongoing and will include satisfaction and utility of nutritionDay 2.0 tools and short-, mid- and long-term effects on the KTA gap. Conclusion: In clinical practice, nutritionDay 2.0 has the potential to promote behavioural and practice changes and improve hospital nutrition care outcomes. In research, the data generated advances knowledge about institutional malnutrition and quality of hospital nutrition care. The ongoing evaluation of the initiative will reveal how far the KTA gap in hospital nutrition care was addressed and facilitate the understanding of the mechanisms needed for successful audit and feedback. Trial registration: Registration in clinicaltrials.gov: Identifier: NCT02820246.